Specular microscopic changes of corneal endothelial cells after phacoemulsification in patients with pseudoexfoliation - Hassan S Yousef; Ibrahim Amer; Shymaa A.A Thabet (Wolters Kluwer Medknow Publications, 2022)
Background and aim Pseudoexfoliation (PEX) syndrome is an age-related ocular disorder that is known to be linked with early development of cataract. Phacoemulsification, a cataract surgery, is thought to carry higher risk of complication in patients with PEX. This study aimed to evaluate the corneal endothelial cell changes before and after phacoemulsification in pseudoexfoliative patients relative to healthy adults. Patients and methods In total, 100 eyes of 100 patients were enrolled in this prospective nonrandomized study who were divided into two groups (PEX and non-PEX patients). All participants were subjected to ocular examination with specular microscopy before and after phacoemulsification. Data for corneal endothelial cell density (ECD), coefficient of variation (CV), and hexagonal cells were recorded before operation and at 1 week, 1 month, and 6 months postoperative. Results No significant difference was detected between the two studied groups regarding ECD, CV, and hexagonality either preoperatively or postoperatively at 1 week, 1 month, and 6 months. However, a significant difference between preoperative and postoperative data of ECD, CV, and hexagonality was detected in each group. Conclusion Despite the previous conviction that phacoemulsification surgery carries more risks in eyes with PEX, the results of this study prove that phacoemulsification is a safe choice in these eyes without a higher rate of postoperative complications.